A COMPARATIVE ANALYSIS OF BUILDING CONSTRUCTION RULES AND THEIR IMPACT ON INDOOR TEMPERATURE OF MULTISTORIED BUILDINGS - Iftekhar Rahman; Md. Mostafizur Rahman (European Scientific Journal, ESJ, 2014)
The International Energy Agency projected that global final energyconsumption in buildings would grow by 30 percent from 2007 to 2030 ifprevailing practices and trends continued. Most of that increase is expectedto come from fast growing developing countries. New buildings in Dhaka arebeing constructed under the 2008 building construction act, termed as 'Dhakamohanagar imarat nirman bidhimala 2008' focusing more on FAR (floor arearatio) offers vertical expansion than horizontal to accommodate the requiredfloor area through providing more open spaces. Increase in building heightswith certain setbacks resulted increase in possibilities of change in naturalindoor lighting at the lower level of the structures. As a result, use ofartificial lighting in indoor spaces may be increased which may result changein fossil fuel consumption for power generation. Beside the indoor daylighting condition the question arises what would be the situation in terms ofindoor temperature due to building to building setback? Is there any impactof indoor temperature due to the setback provided in the construction rulesand the building height achieved in this regard? Thus, this paper tries to findout through theoretical investigation whether there are any impact on indoortemperature at different floor levels due to the direct component of solarradiation; and finds out that building setback and building height due tobuilding regulations influences significantly on indoor temperature atdifferent floor levels within a structure due to direct component of solarradiation. Comparisons between 1996 and 2008 imarat nirman bidhimala arepresented specially for residential buildings. The southwest facade isanalyzed in depeer detail.